Cryo-EM shows stages of initial codon selection on the ribosome by aa-tRNA in ternary complex with GTP and the GTPase-deficient EF-TuH84A. Issue 11 (4th May 2018) - Fislage, Marcus; Zhang, Jingji; Brown, Zuben Patrick; Mandava, Chandra Sekhar; Sanyal, Suparna; Ehrenberg, Måns; Frank, Joachim
Abstract: The GTPase EF-Tu in ternary complex with GTP and aminoacyl-tRNA (aa-tRNA) promotes rapid and accurate delivery of cognate aa-tRNAs to the ribosomal A site. Here we used cryo-EM to study the molecular origins of the accuracy of ribosome-aided recognition of a cognate ternary complex and the accuracy-amplifying role of the monitoring bases A1492, A1493 and G530 of the 16S rRNA. We used the GTPase-deficient EF-Tu variant H84A with native GTP, rather than non-cleavable GTP analogues, to trap a near-cognate ternary complex in high-resolution ribosomal complexes of varying codon-recognition accuracy. We found that ribosome complexes trapped by GTPase-deficicent ternary complex due to the presence of EF-Tu H84A or non-cleavable GTP analogues have very similar structures. We further discuss speed and accuracy of initial aa-tRNA selection in terms of conformational changes of aa-tRNA and stepwise activation of the monitoring bases at the decoding center of the ribosome.